Učne interakcije in sociokognitivni dejavniki učnega uspeha v zadnji triadi osnovne šole - Gril, Alenka (Šolsko polje, 2008)
Teacher's conceptions about teaching have an important impact on the structureof learning interactions, from the point of view of the instruction practice as well as the interpersonal relations in the class. The hypothesis was that the learning interactions effect the formation of students' learning approaches and their achievement in the school. The focus of study was the learning environment (its structure and the class climate) and the sociocognitive factors of teachers and students which could influence the learning process in the class and their impact on the student's achievement inthe last three grades of the elementary school. The classes were followed for the two school years in which the data was collected three times. The regression analysis revealed which factors of learning approaches effected thestudent achievement. The characteristics of learning environment related tothe students' learning approaches and their achievements was analyzed by linear regression as well. The results show that the attributions of the success in learning, the achievement learning goals, the curiosity as the school goal and the educational aspirations are the most powerful predictors of school achievement and are stable through the two school years. The learning environment explained less variance in the students' achievements as in their learning approaches. The most important factors of the learning environment which affected the students' learning approaches and the achievements were related to the peer interactions in the class, the cooperativeness and the competitiveness among students and the peer popularity. Teachers' didactic conceptions and instructions, student gender and the parental level of education were also important predictors of students' learning approaches.
Keywords: motivacija; osnovne šole; raziskave; razredna klima; učenje; učni uspeh; vzgoja in izobraževanje